Flexploitation in The Creative Economy Industry: Implications For Public Policy - Oktari, Tepy; Indiahono, Dwiyanto; Faozanudin, Muslih; Kurniasih, Denok; Tobirin, Tobirin (Department of Public Administration, 2023)
Research into the creative economy industry which brings significant changes in the way individuals work has been widely carried out. However, there is little research on any of the phenomena that appear as side effects of work in this sector. Flexploitation, where creative workers face a high degree of flexibility in their work, but also face economic uncertainty and negative consequences on the resilience of their careers. This article aims to provide a contribution to individuals and stakeholders as a consideration of policy and policy decisions both personally and organizationally, providing a new frame of reference so that it is more about preventive action which is expected to be able to create significant improvements. We analyzed data from existing journals, media articles, statistical data, policies and relevant documents to identify factors contributing to flexploitation and their implications. The results of this research provide the fact that work flexibility, which is always described as a pleasant working condition for the younger generation, both in terms of flexible time and work space in the creative economy industry, actually makes them vulnerable starting from long working hours, lack of social security, and bargaining power. which is very low. This provides valuable input for researchers, practitioners, and organizations as well as policy makers to make improvements. In the smallest sector, this fact provides a stimulus for actors who are already involved in this industry or personal candidates who will soon enter the world of work or a career to be more preventive and think carefully about their own career choices.